Measuring and assessing the impact of the global economic crisis on European real property market - Mach, Łukasz (Journal of Business Economics and Management, 2019)
Economic development of countries, regions or entities operating on the market is possible when favourable economic conditions outweigh adverse conditions. Examining the development of European economy, it is possible to observe this regularity in the majority of periods, i.e. the bull market had a more intense and longer impact on the economy in comparison with the bear market, enabling constant economic development of Europe. Globalisation, a relative ease of financing investment activity, financial over-liquidity, negative interest rates: all of them result in the fact that previously verified and correctly operating mechanisms and market models have become unpredictable. During the latest crisis, the European real property market lost some part of its potential. The loss varied in individual EU member-countries. Some of them coped with the crisis quite successfully, others managed to do so on the average, still others have felt its effects until today. Making use of regressive techniques, the author undertook to measure and assess the impact of the global crisis on the property market. Consequently, the effects and intensity of its impact regarding the number of issued building permits, number of the employed in construction industry, value of construction production and prices of real property were measured.